ANALISIS LARANGAN ABORSI PADA TAFSIR AL-AZHAR: STUDI MAQASID SYARI'AH SURAT AL-ISRA’ AYAT 31 - Jannah, Miftahul; Rahman, Pathur (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2025)
This research is motivated by abortion which has become a crucial issue that has sparked debate among Muslims. In more detail, the formulation of the problem in this research is how to interpret the prohibition on abortion based on Tafsir Al-Azhar by Buya Hamka and maqasid syariah surah al-isra' verse 31. This research uses a qualitative method which is explained descriptively with the aim of explaining and describing a phenomenon or situation what is happening now in detail and in depth. This research uses a maqashid sharia approach to demonstrate the prohibition of abortion and contribute to understanding the ethics of abortion in Islam in Indonesia. It is hoped that the results of this analysis will provide further understanding regarding the prohibition of abortion in depth regarding Islam's views on abortion. This research found that in Surah Al-Isra verse 31 in the Al-Azhar commentary prohibits abortion at all stages of pregnancy. This prohibition is based on Maqashid Sharia, namely the maintenance of soul (nafs), descendants (nasl), reason (aql), religion (din), and property (mal). Buya Hamka's view of opposing the killing of children for fear of poverty is in line with the maqashid sharia principle regarding the protection of the soul. Abortions performed for economic reasons will be considered a violation of life protection. Buya hamka also implies the importance of preserving the lives of children as human descendants. Terminating the life of a fetus without reasons justified according to sharia violates the principle of offspring protection.